Sustaining the future of HIV counselling to reach 90‐90‐90: a regional country analysis. Issue 1 (13th May 2016) - Bemelmans, Marielle; Baert, Saar; Negussie, Eyerusalem; Bygrave, Helen; Biot, Marc; Jamet, Christine; Ellman, Tom; Banda, Amanda; van den Akker, Thomas; Ford, Nathan
Abstract : Introduction: Counselling services are recommended by the World Health Organization and have been partially adopted by national HIV guidelines. In settings with a high HIV burden, patient education and counselling is often performed by lay workers, mainly supported with international funding. There are few examples where ministries of health have been able to absorb lay counsellors into their health systems or otherwise sustain their work. We document the role of lay cadres involved in HIV testing and counselling and adherence support and discuss approaches to sustainability. Methods: We focused on a purposive sample of eight sub‐Saharan African countries where Médecins Sans Frontières supports HIV programmes: Guinea, Lesotho, Malawi, Mozambique, South Africa, Swaziland, Zambia and Zimbabwe. We reviewed both published and grey literature, including national policies and donor proposals, and interviewed key informants, including relevant government staff, donors and non‐governmental organizations. Results and discussion: Lay counsellors play a critical role in scaling up HIV services and addressing gaps in the HIV testing and treatment cascade by providing HIV testing and counselling and adherence support at both the facility and community levels. Countries have taken various steps in recognizing lay counsellors, including harmonizing training, job descriptions and support structures. However, formal integration of this cadre into national health systems is limited, as lay counsellors are usually not included in national strategies or budgeting. Conclusions: The current trend of reduced donor support for lay counsellors, combined with lack of national prioritization, threatens the sustainability of this cadre and thereby quality HIV service delivery.